Epigenome analysis of an algae-infecting giant virus reveals a unique methylation motif catalogue - Alexander R. Truchon; Erik R. Zinser; Steven W. Wilhelm (PLoS ONE, 2025)
DNA methylation can epigenetically alter gene expression and serve as a mechanism for genomic stabilization. Advancements in long-read sequencing technology have allowed for increased exploration into the methylation profiles of various organisms, including viruses. Studies into the Nucleocytoviricota phylum of giant dsDNA viruses have revealed unique strategies for genomic methylation. However, given the diversity across this phylum, further inquiries into specific lineages are necessary. Kratosvirus quantuckense (formerly known as Aureococcus anophagefferens Virus, AaV) is predicted to encode six distinct methyltransferases, which bear homology to other methyltransferases across the many clades of Nucleocytoviricota . We found that the virus’ DNA is methylated with high consistency, including nine different motifs targeted for DNA adenine methylation. Methylation levels varied depending on the associated motif. Likewise, distinct motifs were enriched within unique genomic regions. Collectively our data suggest that each methyltransferase targets unique DNA regions, suggesting they have varying functionality. This work reveals an array of methyltransferase activity in Kratosvirus quantuckense and implicates the importance of DNA methylation to the Nucleocytoviricota infection cycle.